ASSESSMENT OF VILLAGE DEVELOPMENT PRIORITIES AND INNOVATION STRATEGIES USING SWOT ANALYSIS (A STUDY CASE: PASAWAHAN VILLAGE PURWAKARTA REGENCY, WEST JAVA) - Ekawati, June; Rahmawati, Winda (ipdn, 2023)
Village development planning is important to achieve the set goals, but the development of Pasawahan Village so far has not been based on spatial use, so it is unable to answer problems and explore existing local potential. This research aims to study development priorities in spatial planning and village innovation. This research uses a descriptive qualitative method with a SWOT analysis. The research results for priority activities in the development sector include the provision of village health post (poskesdes), a reading garden, and village infrastructure, and the priority in the development empowerment sector is training on appropriate technology for agricultural production, waste processing sites – reduce, reuse, recycle (TPS3R), and village-owned enterprises (BUMDes). Meanwhile, the village innovation strategy is to implement an agrotourism village program. Keywords: Development Planning, Village Development Priorities, Village Innovation